Architetture nel tempo (2015)
Architetture nel tempo represents the awareness of the duration, permanence and authenticity of places along the centuries and in their continuous contemporaneity, entrusted to the preservation which passes on to the future, to the dialogue between ancient and modern architecture and to the restoration project. Therefore, they are not only excellent artefacts, but also everyday architectures, artefacts born of necessity as well as of symbolic and grandiloquent will, which have however survived the passing of time in order to acquire the right to become memory and future, in order to exhibit a citizenship which is equally recognized at the borders of past and present, in order to become that material for history which, through research and investigation in the field, turns itself into history.